Community Education in Areas of Participation, Cooperation and Eco-Development from an Ecofeminist Perspective - Noelia Melero-Aguilar; Dolores Limón-Domínguez (Universidad Nacional, Costa Rica, 2016)
The current ecological crisis leads us to reflect on the developmental model that has been in place in recent decades in capitalist countries, where a conception of progress and modernization has prevailed, altering not only natural, but also social, cultural and, consequently, economic processes. In this sense, our purpose in this article leads us to question the need to promote education that catalyzes personal and structural changes to ensure sustainability and promote awareness among citizens of environmental and developmental issues overall. In defining more just and equitable development alternatives, we approach the role women play in their commitment to the environment, and the search for a better quality of life.